Literasi Digital dan Bela Negara: Resiliensi Generasi Z terhadap Ancaman Non-Militer dalam Perspektif Kebangsaan - Chornelia Citanindya; Tiara Puspa (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
The shifting landscape of global security has expanded national threats beyond traditional military concerns to include complex non-military issues such as disinformation, radicalism, cybercrime, environmental crises, and the moral degradation of younger generations. Indonesia’s status as an archipelagic state with a strategic geopolitical position heightens its vulnerability to these threats, necessitating a multidimensional, participatory national defense approach. Generation Z, Indonesia’s largest productive age group and early digital technology adopters, possesses significant potential for national resilience. However, limited digital literacy exposes them to digital threats. Enhancing digital literacy enables recognition of disinformation, hoaxes, and propaganda, and supports the identification of reliable information. Verifying information before sharing is an essential aspect of national defense in the digital era. Digital literacy also develops Generation Z’s creative and critical thinking regarding information received. This study analyzes Generation Z’s resilience against non-military threats from a national perspective and proposes defense-strengthening strategies. The research employs a qualitative descriptive method, drawing on academic literature, national policies, and survey data. Findings indicate that Generation Z adapts well to technology, but only moderately in digital literacy, increasing susceptibility to weakened nationalism. Reinforcing national values and integrating digital literacy into education emerge as key measures to enhance their resilience. The study concludes that transforming national defense should prioritize strengthening non-military capabilities through digital literacy, national identity, and cross-sector collaboration. These efforts are vital to empower Generation Z in safeguarding Indonesia’s unity in the digital globalization era.